Loss, Hope, and Redemption: The Consequences of Methamphetamine use in a Sample of Incarcerated Women - Gunderman, Mikhial Vincent (2015)
This dissertation examines the consequences of methamphetamine use in a sample of 40 incarcerated women who were court-ordered to participate in a correctional drug and alcohol treatment program in Missouri. Using interview data from this sample, I examine their perceptions of the consequences of their methamphetamine use. The negative consequences I focus on include experiences of violence, damage to interpersonal relationships, and more personal consequences related to health, employment, housing, and the criminal justice system. In this pursuit, I explore the following research questions: 1) What is the relationship between the accumulation of negative consequences and continued and/or increased involvement in drug use and illicit activity?; and 2) How do former methamphetamine users hope to remain desisted from involvement in drug use and illicit activity upon their release from prison/treatment? In order to accomplish these goals, I draw on the life course perspective to help explain the processes of persistence and desistance over the life course. Ultimately, I show how negative consequences related to these women’s methamphetamine use compound and result in the creation of a state of cumulative continuity. Cumulative continuity is a cycle of accumulating negative consequences resulting in continued, and often times increased, drug use and illicit activity. Additionally, I show how this group of women hopes to desist from drug use and illicit activity through identity transformation with goals of normalcy and conventionality related to the process of “making good.